Preparation of spherical cross‐linked lipase aggregates with improved activity, stability and reusability characteristic in water‐in‐ionic liquid microemulsion. Issue 7 (20th January 2017) - Cui, Jiandong; Lin, Tao; Feng, Yuxiao; Tan, Zhilei; Jia, Shiru
Abstract: BACKGROUND: Cross‐linking enzyme aggregates (CLEAs) seem to be a promising immobilization method due to mild processing conditions and short preparation time. However, the CLEAs prepared in aqueous solution exhibit amorphous large clusters that cause significant mass‐transfer limitations, leading to low catalytic efficiency. In this work, novel spherical CLEAs of lipase from bovine pancreas (spherical CLEAs) were prepared within droplets dispersed in a water‐in‐hydrophobic ionic liquid microemulsion rather than a conventional aqueous solution. The properties of the spherical CLEAs were determined. RESULTS: The resultant CLEAs exhibited spherical structure with good monodispersity instead of the amorphous clusters of conventional CLEAs, and showed higher activity recovery (84.6%) than that of conventional CLEAs (52.8%). The high activity recovery of spherical CLEAs could be attributed to both interfacial activation of the microemulsion system and the well‐defined structure of the spherical CLEAs, which not only activated lipases in an active form, but also decreased mass‐transfer limitations. Moreover, the thermostability, storage stability, tolerance against hydrophilic solvents, and mechanical stability of the spherical CLEAs were enhanced significantly. The spherical CLEAs evidenced excellent reusability in comparison with conventional CLEAs. CONCLUSIONS: The novel strategy in this study might open an attractive way towards effectively improving the catalytic properties of traditional CLEAs. © 2016 Society of Chemical Industry